Tindak Tutur Direktif dalam Naskah Drama Harut dan Marut Karya Ali Ahmad Bakatsir (Kajian Pragmatik) - Fendi Utomo (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
Drama scripts are different from novels or short stories. In the drama script, there are types of speech acts with different functions. Likewise in the drama script Harut and Marut by Ali Ahmad Bakatsir, in it there are many types of speech found, especially the types of speech that are included in directive speech acts. The only way to find out the types and functions of the utterances in the dialogue between the characters is to use speech act theory in pragmatic studies. So this study aims to describe the types and functions of directive speech acts in Harut and Marut drama scripts. In this study, the data collection method used was the note-taking method. The data obtained were then analyzed using a qualitative descriptive method. The speech act theory used by the researcher in this research is the theory proposed by Muhammad Sharraf. Muhammad Sharraf divides directive speech acts into two, namely thalabiyyah directive speech acts and nafsiyyah directive speech acts. The results of this study indicate that in the drama script Harut and Marut there are two types of directive speech acts, namely thalabiyyah directive speech acts whose functions include; to command, ask permission, threaten, plead, and forbid. As well as nafsiyyah directive speech acts whose functions include; to curse, complain, and soothe.